Community Vital Signs. Issue 7 (28th August 2019) - Kaufman, Roger
Abstract: Vital signs are the objective variables and measurable criteria for any city that cares deeply about its value to residents. They are similar to the vital signs that physicians use to assess your health status. For a city to measure community vital signs, it must determine what it does and delivers and must assess how residents perceive and determine what the city's services and policies are delivering. Citizen involvement is essential. This article provides possibly useful vital signs derived from communities around the world.